Immediate Endosseous Dental Implant Placement in Osteocutaneous Radial Forearm Free Flap. (2nd September 2014) - Moneta, Lauren B.; Peck, Jessica J.; Eftekhari, Siavash; Petrisor, Daniel; Wax, Mark K.
Abstract : Objectives: (1) Analyze the advantages and disadvantages of immediate endosseous dental reconstruction using osteocutaneous radial forearm free flap (OCRFFF). (2) Describe the "double barrel" technique for dental reconstruction following OCRFFF. Methods: A 61‐year‐old man with previous hard palate squamous cell carcinoma (SCC) and fibula flap reconstruction complicated by osteoradionecrosis then underwent OCRFFF for secondary reconstruction of the maxilla using the "double barrel" technique. The Straumann system was used to immediately place 3 endosseus implants in the radial bone graft and one in the previously bone‐grafted site. The purpose of this case report is to evaluate the methodology and outcome of immediate dental reconstruction with endosseous implants into an OCRFFF, which is traditionally thought to be an unsuitable graft for dental implants because of inadequate bone thickness. Outcome measures include hardware stability, aesthetics, and function. Aesthetics and function were subjectively measured through patient and surgeon satisfaction. Additionally, hardware stability was measured through follow‐up imaging studies and functionality. Results: Both patients and physicians concluded positive functional and aesthetic outcomes using this reconstruction technique. Conclusions: Use of a double‐barrel technique harvest of an OCRFFF provides adequate bone for immediate endosseus dental implants with improved aesthetic and functional outcomes over other reconstructive techniques.